A Study of Values among Trainee Teachers in Relation to Their Academic Achievement - Aggarwal, Vandana; Kaur, Raskirat (International Journal of Psychosocial Rehabilitation, 2020)
Education is the context of social changes is not only to impart information and to teach skills to the students but also to inculcate the values of humanism, democracy, socialism, secularism and national integration. This is necessary for realization of our national objectives of building a democratic and just social order based on equality, social justice, fraternity and freedom. Several educationists in India and abroad have stressed the importance of promoting values through education, which is facing the crisis of character in different spheres of life. Value education is a many sided Endeavour as value itself. The theory and practice of value education are emotional and teach some forty to sixty lessons in various classes in school subjects in which one specializes of these a few lessons may be directly related to the concepts of population education or may be modified to population awareness content in subjects thus providing opportunity to the teacher to acquire necessary skills of integrating population education in existing curricula.